CHILD MARRIAGE DISPENSATION FROM THE PERSPECTIVE OF CHILD PROTECTION - Lailatul Magfiroh; Erny Herlin Setyorini (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Child marriage dispensation in Indonesia is regulated under Law No. 16 of 2019 and can only be granted under urgent circumstances. Social phenomena, such as premarital pregnancy and cultural pressures, create a dilemma between legal compliance and the protection of children’s rights. This study aims to analyze the judicial practice of child marriage dispensation at the Surabaya Religious Court through case studies of Decision No. 5/Pdt.P/2025/PA.Sby and No. 2194/Pdt.P/2024/PA.Sby. The research employs a qualitative descriptive approach, analyzing court documents, limited interviews with relevant parties, and reviewing literature on law and child protection. The findings reveal differences in judges’ considerations. In case 5/Pdt.P/2025, the dispensation was granted due to the child’s pregnancy, with primary considerations on protecting the child and the unborn, reducing social stigma, and ensuring the continuation of the child’s education. Conversely, case 2194/Pdt.P/2024 focused on social and cultural family reasons without urgent biological conditions, resulting in limited attention to the child’s educational and psychological needs. Both cases highlight the lack of professional psychological assessment, minimal involvement of child protection agencies, and variation in interpreting “urgent reasons.” The study emphasizes the need for clearer operational guidelines, transparent documentation of judicial reasoning, and a multidisciplinary approach to consistently uphold the best interests of the child principle. These findings can inform national policy reform, strengthen post-decision monitoring, and enhance public awareness regarding child marriage dispensation